A systematic genome-wide analysis of zebrafish protein-coding gene function - Kettleborough, Ross N. W. (2013)
Since the publication of the human reference genome, the identities of specific genes associated with human diseases are being discovered at an enormous rate. A central problem is that the biological activity of these genes is often unclear. Detailed investigations in vertebrate model organisms, typically mice, have been essential for understanding the activities of many orthologues of these disease-associated genes. Although gene-targeting approaches(1-3) and phenotype analysis have led to a detailed understanding of nearly 6,000 protein-coding genes(3,4), this number falls significantly short of all >22,000 mouse protein-coding genes(5). Similarly, in zebrafish genetics, one-by-one gene studies using positional cloning(6), insertional mutagenesis(7-9), antisense morpholino oligonucleotides(10), targeted re-sequencing(11-13) and zinc finger and TAL endonucleases(14-17) have made significant contributions to our understanding of the biological activity of vertebrate genes, but the number of genes studied again falls well short of the >26,000 zebrafish protein-coding genes(18). Importantly, for both mice and zebrafish, none of these strategies is particularly suited to the rapid generation of knockouts in thousands of genes and the assessment of their biological activity. Enabled by a well-annotated zebrafish reference genome sequence(18,19), high-throughput sequencing and efficient chemical mutagenesis, we describe an active project that aims to identify and phenotype disruptive mutations in every zebrafish protein-coding gene. Thus far we have identified potentially disruptive mutations in more than 38% of all known protein coding genes. We have developed a multi-allelic phenotyping scheme to efficiently assess the effects of each allele during embryogenesis and have analysed the phenotypic consequences of over 1000 alleles. All mutant alleles and data are available to the community and our phenotyping scheme is adaptable to phenotypic analysis beyond embryogenesis.